Structural, chemical and optical properties of SnO2 NPs obtained by three different synthesis routes. (August 2017) - Drzymała, Elżbieta; Gruzeł, Grzegorz; Depciuch, Joanna; Budziak, Andrzej; Kowal, Andrzej; Parlinska-Wojtan, Magdalena
Abstract: Polyol (P), chemical precipitation (C) and microwave-assisted (M) syntheses were chosen to produce SnO2 nanoparticles with uniform size and minimum agglomeration. Their structural, chemical and optical properties were investigated using dynamic light scattering (DLS), scanning transmission electron microscopy (STEM), Raman, Fourier Transform Infrared (FTIR) using the Attenuated Total Reflectance (ATR) technique and Ultraviolet–Visible (UV–Vis) spectroscopies. STEM observations showed that the SnO2 (P) and SnO2 (C) nanoparticles (NPs) are combined into larger agglomerates with heterogeneous thickness, while the microwave-assisted NPs form a uniform thin layer across the TEM grid. The strongest agglomeration of the SnO2 (C) NPs, observed by DLS, STEM and UV–Vis is explained by the very moderate amount of water present on the surface of the NPs identified by FTIR spectroscopy. High resolution STEM combined with SAED and X-ray diffraction (XRD) patterns confirmed the crystalline character of the NPs. In the nanoparticles from polyol synthesis, chlorine from the remains of metal precursors during reduction was detected by energy dispersive spectroscopy (EDS), contrary to the NPs obtained by the chemical precipitation and microwave-assisted methods. All three syntheses routes lead to small, 2–10 nm SnO2 NPs, which were the result of the low concentration of Cl ions in the solutions. Highlights: Small size (2–10 nm) SnO2 NPs were obtained by the three different synthesis methods Best crystallinity of SnO2 NPs chemical precipitation and microwave methods With increasing the synthesis time SnO2 NPs obtained by the polyol method were crystalline Strong agglomeration of SnO2 NPs obtained by chemical precipitation method